الأتجاه العقلي في تفسیر القرآن الکریم: The Rational Approach in the Interpretation of the Holy Quran (Khairulummah, 2023)
The rational approach in interpreting the Holy Quran is a methodology that relies on reason, logic, and contemplation. Its aim is to understand the meanings of Quranic verses through rational arguments and reflection upon the Quranic texts.Reactions towards the rational interpretation approach vary, as some individuals reject it, believing that the interpretation based on transmitted reports (Athar) is the only correct method. On the other hand, others accept it, seeing that the utilization of reason enhances our understanding of the religion and makes it more applicable in daily life.The truth is that the correct rational approach in interpreting the Quran depends on the harmonious combination of reason and transmitted reports, relying on language and Quranic context, and adhering to the concepts derived from the Quranic texts.Conversely, the deviant rational approach in interpreting the Holy Quran deviates from the correct rational methodology. This deviation can occur due to excessive reliance on reason while neglecting the Quranic texts or misinterpreting them, being influenced by baseless philosophical concepts, or having personal biases and desires to interpret the Quran according to personal interests and whims.